BUDAYA ORGANISASI, KOMITMEN ORGANISASIONAL PIMPINAN DAN PENGARUHNYA TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN BANK - Sopiah Sopiah (University of Merdeka Malang, 2008)
This study was intended to reveal the effect of organizational Culture andorganizational leaders commitment toward employee job satisfaction and the effect towardemployee performance. The study was carried out by taking the population of employee in allSyariah banks in Malang City, with the number of population was 1881 employee and 200samples were taken with random sampling. Questionnaire was used to obtain data, and toanalysis the data, SEM analysis and AMOS program were applied. The result of study indicatedthat: (1) there was an effect of organizational culture toward syariah bank employee jobsatisfaction (2) there was an effect of organizational culture toward syariah bank employeeperformance (3) there was an effect of leaders commitment toward employee job satisfaction(4) there was an effect of leaders commitment toward syariah bank employee performance (5)there was an effect of job satisfaction toward syariah bank employee performance (6) therewas an effect of organizational culture toward syariah bank employee performance throughjob satisfaction (7) there was an effect of leaders commitment toward employee performancethrough instructors job satisfaction. Empirically this study was proved significant, thereforethe management of Syariah Bank in Malang City was expected to develop organizationalculture and leaders commitment should have paid attention to Islamic values beside applyingcontemporary management approach from western culture, in the effort to build employeesyariah bank job satisfaction and hopefully it would have an effect in the increase of employeeperformance improvement.